2000
DOI: 10.1055/s-2000-8356
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment EEG and It's Relationship to Depression Severity and Paroxetine Treatment Outcome

Abstract: An array of variables have been assessed as potential early predictors of antidepressant response in depressed patients. This exploratory study examined the relationship of clinical outcome, following pharmacotherapeutic treatment, with quantitative electroencephalographic (EEG) features assessed prior to treatment onset. In 70 major affective disorder patients, pre-treatment spectrum-analysed topographic EEG indices (absolute power, relative power, mean frequency, inter-hemispheric power asymmetry and coheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(59 citation statements)
references
References 20 publications
7
50
0
2
Order By: Relevance
“…Responders and non-responders did not differ concerning sub-stage B2/3 which is characterized by dominant theta band activity. In line with that, other research groups found no differences in absolute or relative theta power38 or a decreased theta power in responders to antidepressants3940. Owing to the fact that another study found decreased theta activity to be associated with non-response41, the heterogeneity in results was recently explained with the origins of the measured theta activities14: the reduced widespread frontal activity within the responders3839 was ‘considered most likely’ as a sign of reduced drowsiness which may not be the case in the study investigating frontal midline theta activity41.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Responders and non-responders did not differ concerning sub-stage B2/3 which is characterized by dominant theta band activity. In line with that, other research groups found no differences in absolute or relative theta power38 or a decreased theta power in responders to antidepressants3940. Owing to the fact that another study found decreased theta activity to be associated with non-response41, the heterogeneity in results was recently explained with the origins of the measured theta activities14: the reduced widespread frontal activity within the responders3839 was ‘considered most likely’ as a sign of reduced drowsiness which may not be the case in the study investigating frontal midline theta activity41.…”
Section: Discussionsupporting
confidence: 60%
“…In line with that, other research groups found no differences in absolute or relative theta power38 or a decreased theta power in responders to antidepressants3940. Owing to the fact that another study found decreased theta activity to be associated with non-response41, the heterogeneity in results was recently explained with the origins of the measured theta activities14: the reduced widespread frontal activity within the responders3839 was ‘considered most likely’ as a sign of reduced drowsiness which may not be the case in the study investigating frontal midline theta activity41. For theta activity specifically assessed within the anterior cingulate cortex, results are again contradictory with both decreased and increased activity to be favourable for treatment outcome111213.…”
Section: Discussionsupporting
confidence: 60%
“…The observed increased theta in the ACC may reflect increased metabolism in the ACC in response to effective treatment [78]. An increase in alpha wave activity has also been reported in depressed patients who are not on medication [75,79], and those who respond to SSRI treatment have detectable differences in alpha wave characteristics when compared to non-responders [8082]. These observations support the idea that EEG measures may be informative for tracking treatment response.…”
Section: Neuroimaging and Electroencephalography Biomarkersmentioning
confidence: 61%
“…The MDD patients with greater theta and lower beta band activities were R compared to NR [98]. Furthermore, an increase in the left frontal theta activity compared to baseline was reported after electroconvulsive therapy (ECT) [100].…”
Section: Theta Band Activationsmentioning
confidence: 93%
“…In contrast, a study reported increased alpha power associated with R with 29 MDD patients who were treated with imipramine for 6 weeks [42]; however, the study did not provide any statistical support. In addition, an increase in the alpha power accompanied with a decrease in the theta power among R compared with NR was reported, including paroxetine administration for 50 MDD patients for 6 weeks [98].…”
Section: Alpha Power and Alpha Asymmetrymentioning
confidence: 95%